Baseline assessment of cervical cancer screening and treatment capacity in 25 counties in Kenya, 2022 - Mwenda, Valerian; Murage, David; Kilonzo, Catherine; Bor, Joan-Paula; Njiri, Patricia; Osiro, Lance; Nyangasi, Mary; Arbyn, Marc; Tummers, Philippe; Temmerman, Marleen (Frontiers in Oncology, 2024)
Background Cervical cancer is the leading cause of cancer deaths among women in Kenya. In the context of the Global strategy to accelerate the elimination of cervical cancer as a public health problem, Kenya is currently implementing screening and treatment scale-up. For effectively tracking the scale-up, a baseline assessment of cervical cancer screening and treatment service availability and readiness was conducted in 25 priority counties. We describe the findings of this assessment in the context of elimination efforts in Kenya. Methods The survey was conducted from February 2021 to January 2022. All public hospitals in the target counties were included. We utilized healthcare workers trained in preparation for the scale-up as data collectors in each sub-county. Two electronic survey questionnaires (screening and treatment; and laboratory components) were used for data collection. All the health system building blocks were assessed. We used descriptive statistics to summarize the main service readiness indicators. Results Of 3,150 hospitals surveyed, 47.6% (1,499) offered cervical cancer screening only, while 5.3% (166) offered both screening and treatment for precancer lesions. Visual inspection with acetic acid (VIA) was used in 96.0% (1,599/1,665) of the hospitals as primary screening modality and HPV testing was available in 31 (1.0%) hospitals. Among the 166 hospitals offering treatment for precancerous lesions, 79.5% (132/166) used cryotherapy, 18.7% (31/166) performed thermal ablation and 25.3% (42/166) performed large loop excision of the transformation zone (LLETZ). Pathology services were offered in only 7.1% (17/238) of the hospitals expected to have the service (level 4 and above). Only 10.8% (2,955/27,363) of healthcare workers were trained in cervical cancer screening and treatment; of these, 71.0% (2,097/2,955) were offering the services. Less than half of the hospitals had cervical cancer screening and treatment commodities at time of survey. The main health system strength was presence of multiple screening points at hospitals, but frequent commodity stock-outs was a key weakness. Conclusion Training, commodities, and diagnostic services are major gaps in the cervical cancer program in Kenya. To meet the 2030 elimination targets, the national and county governments should ensure adequate financing, training, and service integration, especially at primary care level.